2021
DOI: 10.3390/cancers13051145
|View full text |Cite
|
Sign up to set email alerts
|

Novel Combinatorial Approaches to Tackle the Immunosuppressive Microenvironment of Prostate Cancer

Abstract: Prostate cancer (PCa) is the second-most common cancer in men worldwide and treatment options for patients with advanced or aggressive prostate cancer or recurrent disease continue to be of limited success and are rarely curative. Despite immune checkpoint blockade (ICB) efficacy in some melanoma, lung, kidney and breast cancers, immunotherapy efforts have been remarkably unsuccessful in PCa. One hypothesis behind this lack of efficacy is the generation of a distinctly immunosuppressive prostate tumor microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 218 publications
(227 reference statements)
0
16
0
Order By: Relevance
“…For a prevalent illness like PCa, little is known about its genesis, and only a few risk factors have been discovered ( Lin et al, 2021 ). Several factors are responsible for changes in its prevalence at the regional level due to changes in the susceptibility of different population groups to environmental risk factors, including racial/ethnic backgrounds, geographical heterogeneity, advancing age and an intact hypothalamic-pituitary-gonadal axis, family history, genetic mutations (e.g., BRCA1 and BRCA2), and diagnosis and access to good quality treatment ( Hoimes and Kelly, 2009 ; Rebbeck et al, 2013 ; Shackleton et al, 2021 ). PCa incidence and death rates differ significantly between ethnic groups, implying ethnic and genetic susceptibility ( Shackleton et al, 2021 ).…”
Section: Castration-resistant Prostate Cancermentioning
confidence: 99%
“…For a prevalent illness like PCa, little is known about its genesis, and only a few risk factors have been discovered ( Lin et al, 2021 ). Several factors are responsible for changes in its prevalence at the regional level due to changes in the susceptibility of different population groups to environmental risk factors, including racial/ethnic backgrounds, geographical heterogeneity, advancing age and an intact hypothalamic-pituitary-gonadal axis, family history, genetic mutations (e.g., BRCA1 and BRCA2), and diagnosis and access to good quality treatment ( Hoimes and Kelly, 2009 ; Rebbeck et al, 2013 ; Shackleton et al, 2021 ). PCa incidence and death rates differ significantly between ethnic groups, implying ethnic and genetic susceptibility ( Shackleton et al, 2021 ).…”
Section: Castration-resistant Prostate Cancermentioning
confidence: 99%
“…CD8+ cytotoxic T lymphocytes isolated from prostate cancer appear to have undergone clonal expansion in response to a certain antigen as they exhibit restricted T cell receptor Vβ gene usage 25 ; however, in some patients, near 90% of these prostate‐infiltrating CD8+ T cells are positive for programmed cell death protein 1 (PD‐1), 25 a cell surface immune‐suppressive checkpoint protein associated with self‐tolerance by suppressing T cell immune activity. These PD‐1 expressing cytotoxic T cells are likely incapable of mounting an effective immune response 25–28 . Cytotoxic T cell activity of killing tumor cells can also be weakened by the cancer cell production of decoy molecules against Fas and TRAIL‐induced death pathways (i.e., decoy receptor 3 [DcR3] and decoy receptor 4 [DcR4, aka TRAILR4]) 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regulatory T (T reg ) cells and their expression of immune checkpoint cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) may also play pivotal roles in suppressing the antitumor immunity in prostate cancer. A study showed that upregulation of CTLA4 and its mediated immune tolerance were identified in more than half of prostate cancer patients 28 . Among prostate cancer patients with immunologic ignorance, more than 10% had a combination of PD‐1, CTLA4, and DcR3 all three mechanisms 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cancers, including PCa, are known to elicit an overproduction of a range of immunocyte suppressors, including immature myeloid cells, which recently were categorized as myeloid-derived suppressor cells (MDSCs) [14][15][16][17]. Tumor excision response of MDSC in PCa patients has also been reported [15].…”
Section: Introductionmentioning
confidence: 99%